Balancing Profit and Planet: The Impact of Green Marketing on Brand Performance - Rofiq, Ainur; Amanda, Gia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – The growing consumer awareness of environmental issues has driven companies to adopt more environmentally responsible business strategies. This research aims to describe the implementation of green marketing strategies by Curcuma Plus, a well-known children’s multivitamin brand, and assess their impact on the brand’s sustainability. Design/methodology/approach – The data for this qualitative descriptive study were collected through interviews, observations, and document analysis. Findings – The findings indicate that Curcuma Plus has achieved a